2016
DOI: 10.3390/ma9050399
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Carbide Nanofibers-Reinforced Aluminum Compacts, a New Strategy to Enhance Mechanical Properties

Abstract: TiC nanofibers reinforced Al matrix composites were produced by High Frequency Induction Heat Sintering (HFIHS).The titanium carbide nanofibers with an average diameter of 90 nm are first prepared by electrospinning technique and high temperature calcination process. A composite solution containing polyacrylonitrile and titanium isopropoxide is first electrospun into the nanofibers, which are subsequently stabilized and then calcined to produce the desired TiC nanofibers. The X-ray diffraction pattern and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The use of Ti-base alloys in various fields comes from its super biocompatibility, excellent mechanical properties, and great corrosion resistance in many aggressive environments [10][11][12][13][14]. The use of titanium alloys in offshore structures and marine applications results from it low density, superior strength, and extremely high resistance to corrosion [2,3,[15][16][17][18][19][20]. Another important usage of titanium alloys is as an outstanding and strong material in the field of biomedical implantations [8][9][10][11][12][13][14][15]21].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Ti-base alloys in various fields comes from its super biocompatibility, excellent mechanical properties, and great corrosion resistance in many aggressive environments [10][11][12][13][14]. The use of titanium alloys in offshore structures and marine applications results from it low density, superior strength, and extremely high resistance to corrosion [2,3,[15][16][17][18][19][20]. Another important usage of titanium alloys is as an outstanding and strong material in the field of biomedical implantations [8][9][10][11][12][13][14][15]21].…”
Section: Introductionmentioning
confidence: 99%
“…Ti-base alloys have exceptional properties such as excellent mechanical properties, great biocompatibility, and outstanding corrosion resistance against various aggressive electrolytes [1][2][3][4][5]. For that, these alloys have been employed as a standard engineering materials in numerous industrial applications such as their potential use in medical, military, marine, and offshore application [4][5][6][7][8]. The fact that the good corrosion resistance to most corrosive media, the low density, and the high strength make various titanium alloys applicable to be employed in the marine industries and offshore structures [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For that, these alloys have been employed as a standard engineering materials in numerous industrial applications such as their potential use in medical, military, marine, and offshore application [4][5][6][7][8]. The fact that the good corrosion resistance to most corrosive media, the low density, and the high strength make various titanium alloys applicable to be employed in the marine industries and offshore structures [4][5][6][7][8]. The excellent corrosion resistance accounted for the Ti-base alloys has been claimed due to the surfaces of these materials having the ability to develop and form a continuous, highly adherent, stable, and protective titanium oxide layer (TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be seen that the ACNFs possessed rougher, irregular, and undulated structure compared to NFs prior activation. The average diameter of the all NFs also decreased up to 40% from 450 nm to 270 nm due to the removal of PAN and other molecules during the heat treatment resulting in weight loss and NFs' diameter reduction [8,9]. As shown in Figure 2 Although this result counterback the result of previous research conducted by Dadvar et al [6], as they said the increasing the amount of metal oxide loaded, the smaller the diameter of the NFs; this study has concluded that NFs were only affected by the amount of metal oxide, which is up to its maximum loading depends on the type of the metal oxide used in order to produce NFs with better structure.…”
Section: Resultsmentioning
confidence: 99%